Abrupt climatic events recorded by the Ili loess during the last glaciation in Central Asia: Evidence from grain-size and minerals. (15th April 2018) - Song, Yougui; Zeng, Mengxiu; Chen, Xiuling; Li, Yue; Chang, Hong; An, Zhisheng; Guo, Xiaohua
Graphical abstract: Highlights: High-resolution climatic fluctuations inferred from the Ili loess. Shifting of westerlies played an important role in dust deposition. Westerlies transmitted North Atlantic climatic signals from Central Asia to East Asia. Abstract: The loess record of Central Asia provides an important archive of regional climate and environmental changes. In contrast to the widely investigated loess deposits in the Chinese Loess Plateau, Central Asian loess–paleosol sequences remain poorly understood. Here, we present an aeolian loess section in the southern Ili Basin. Based on granularity and mineralogical analyses, we reconstruct climatic changes during the last glaciation. The results indicated that most of the abrupt climatic events (such as Dansgaard-Oeschger events and Heinrich events) were imprinted in this loess section, although their amplitudes and ages showed some differences. Compared with the millennial oscillations recoded in loess and stalagmites in East Asia, the arid Central Asia responded more sensitively to the warming events than to the cooling events. The shifting trajectory of westerlies across Central Asia played an important role in dust deposition during the stadials. The North Atlantic climatic signals may have been transmitted from Central Asia to the East Asian monsoon regions via the westerlies.